pH-Sensitive carboxymethyl chitosan-modified cationic liposomes for sorafenib and siRNA co-delivery - Yao Y (Dove Medical Press, 2015)
Yao Yao, Zhihui Su, Yanchao Liang, Na Zhang School of Pharmaceutical Sciences, Shandong University, Jinan, Shandong, People’s Republic of China Abstract: Combination of chemotherapeutic drug and small interfering RNA (siRNA) can affect multiple disease pathways and has been proven effective in suppressing tumor progression. Co-delivery of drug and siRNA within a same nanocarrier is a vital means in this field. The present study aimed at the development of a pH-sensitive liposome to co-deliver drug and siRNA to tumor region. Driven by the electrostatic interaction, the pH-sensitive material, carboxymethyl chitosan (CMCS), was coated onto the surface of the cationic liposome (CL) preloaded with sorafenib (Sf) and siRNA (Si). To evaluate whether the resulting CMCS-modified Sf and siRNA co-delivery cationic liposome (CMCS-SiSf-CL) enhanced antitumor efficiency after systematic administration, in vitro and in vivo experiments were evaluated in HepG2 cells and the H22 cells-bearing Kunming mice model. The experimental results demonstrated that CMCS-SiSf-CL was able to condense siRNA efficiently and protect siRNA from being degraded by serum and RNase. The release rate of Sf from CMCS-modified liposome exhibited pH-sensitive release behavior. Furthermore, in vitro cellular uptake results showed that CMCS-SiSf-CL yielded higher fluorescence intensity at pH 6.5 than at pH 7.4, and that siRNA could be delivered to tumor site by CMCS-SiSf-CL in vivo. The in vivo antitumor efficacy showed that CMCS-Sf-CL inhibits tumor growth effectively when compared with free Sf solution. In current experimental conditions, this liposomal formulation did not show significant toxicity both in vitro and in vivo. Therefore, co-delivering Sf with siRNA by CMCS-SiSf-CL might provide a promising approach for tumor therapy. Keywords: co-delivery, sorafenib, gene, charge conversion, cancer therapy